2000
DOI: 10.1016/s0001-2092(06)62184-4
|View full text |Cite
|
Sign up to set email alerts
|

Effective pain management in older patients

Abstract: Assessing and managing post-operative pain in older adult patients is complex. A baseline preoperative pain assessment provides the necessary data that assist appropriate and effective pain management. Careful monitoring and individualization of patient dosages result in effective older adult patient pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Some staff have experienced the use of pain-assessment tools in the acute setting and would like to see them put into practice within the care home. Those who have studied staff perceptions in care home settings do support the concept that the staff are keen to improve the situation, as found within the current study, but often time was a limiting factor (23,36,37) and others suggested that education within the care home setting was poor for all levels of staff.…”
Section: Doing Moresupporting
confidence: 60%
“…Some staff have experienced the use of pain-assessment tools in the acute setting and would like to see them put into practice within the care home. Those who have studied staff perceptions in care home settings do support the concept that the staff are keen to improve the situation, as found within the current study, but often time was a limiting factor (23,36,37) and others suggested that education within the care home setting was poor for all levels of staff.…”
Section: Doing Moresupporting
confidence: 60%
“…How they are handling the pain may be perceived as preferable to the side effects and costs of treatments (Ward et al, 1993). Communication barriers result from beliefs that nurses are too busy to listen or to help (Yates, Dewar, & Fentiman, 1994), that talking about pain will label people as "complainers" (Lin, 2000), and that being stoic is preferable to worrying others about their pain (Larsen, 2000;Martin, 1998;Ruzicka, 1998).…”
Section: Pain Management Barriersmentioning
confidence: 99%
“…Small doses of pain medications should be given at regular intervals, with additional doses given for breakthrough pain 19 . Individualize opioid doses by starting slow and titrating up based on the patient's response and any side effects noted 20 . Meperidine HCl, propoxyphene HCl, and pentazocine all should be avoided in older adults because they can impair renal function and increase the risk of delirium 21…”
Section: Case Studymentioning
confidence: 99%